Tokoh Al-Washliyah: Syekh Ismail Banda dan Perjuangannya dalam Diplomasi dan Pendidikan - Ramadhani, Suci; Harahap, Donna Sapitri; Siregar, Yusra Dewi (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2024)
This study explores the figure of Syekh Ismail Banda as one of the prominent leaders of the Al-Washliyah organization, who played a significant role in the fields of diplomacy and education during both the pre- and post-independence periods of Indonesia. The aim of this research is to investigate the contributions and struggles of Syekh Ismail Banda in strengthening Al-Washliyah's role as a religious institution and an agent of social transformation through diplomatic efforts and the advancement of Islamic education. A qualitative method was employed, using literature review and historical document analysis related to Syekh Ismail Banda’s activities as a scholar, educator, and informal diplomat. The findings reveal that Syekh Ismail Banda played a strategic role in expanding Al-Washliyah’s da’wah network and establishing Islamic educational institutions in North Sumatra. Furthermore, he actively engaged with national and international figures to advocate for the interests of the Muslim community, both locally and globally. His diplomatic endeavors were evident in his conflict mediation efforts, participation in religious forums, and advocacy for Islamic educational policies. In the field of education, he is recognized as the founder of several madrasahs and a pioneer in strengthening curricula based on moderate Islamic values. This study concludes that Syekh Ismail Banda was a visionary figure who successfully integrated religious values, education, and diplomacy as the foundation of his struggle to build an empowered and knowledgeable Muslim society. His legacy remains relevant today as a source of inspiration for the development of Islamic education and cultural diplomacy in Indonesia.